2014
DOI: 10.1002/chem.201405729
|View full text |Cite
|
Sign up to set email alerts
|

Iridium Catalyzed Carbocyclizations: Efficient (5+2) Cycloadditions of Vinylcyclopropanes and Alkynes

Abstract: Third-row transition metal catalysts remain a largely untapped resource in cycloaddition reactions for the formation of medium-sized rings. Herein, we report the first examples of iridium-catalyzed inter- and intramolecular vinylcyclopropane (VCP)-alkyne (5+2) cycloadditions. DFT modeling suggests that catalysis by iridium(I) proceeds through a mechanism similar to that previously reported for rhodium(I)-catalyzed VCP-alkyne cycloadditions, but a smaller free energy span for iridium enables substantially faste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 50 publications
1
30
0
Order By: Relevance
“…[3,4] In 1995, Wender et al first reported the intramolecular rhodium-catalyzed cycloaddition of VCPs with alkynes. [10] In addition, the intermolecular cycloadditions of VCPs with p-systems [11][12][13] and other transition metal catalyzed [5+ +2] cycloadditions [14,15] have been reported. [10] In addition, the intermolecular cycloadditions of VCPs with p-systems [11][12][13] and other transition metal catalyzed [5+ +2] cycloadditions [14,15] have been reported.…”
mentioning
confidence: 99%
“…[3,4] In 1995, Wender et al first reported the intramolecular rhodium-catalyzed cycloaddition of VCPs with alkynes. [10] In addition, the intermolecular cycloadditions of VCPs with p-systems [11][12][13] and other transition metal catalyzed [5+ +2] cycloadditions [14,15] have been reported. [10] In addition, the intermolecular cycloadditions of VCPs with p-systems [11][12][13] and other transition metal catalyzed [5+ +2] cycloadditions [14,15] have been reported.…”
mentioning
confidence: 99%
“…[3][4][5][6] Meanwhile,t he intramolecular VCP/alkyne cycloaddition has also been catalyzed by other transition metals, such as ruthenium, [7] nickel, [8] iron, [9] and iridium. [10] Depending on the transition metal, the VCP/alkyne cycloaddition is proposed to involve either alkyne/alkene oxidative cyclization to form am etallacyclopentene A (for Ru, [11] Ni, [12] and Fe [9] )orcyclopropane cleavage to form ametallacyclohexene B (for Rh [13] and Ir [10] )a st he initial step (Scheme 1). Intermediates A and B would converge to am etallacyclooctadiene C through b-carbon elimination and migratory insertion, respectively,a nd C À Cr eductive elimination of this common intermediate would lead to the cycloheptadiene product.…”
mentioning
confidence: 99%
“…[1] More recently,d bCOT has found prominence as ab is-h 2 -ligand that confers exceptionalc atalytic activity and stabilityt ol ate transition metals. Notable examples in which dbCOT-metal complexes are known to exhibit superiorp erformance in catalysis spansi ridium(I)-catalyzed allylic substitutions, [2] rhodium(I)catalyzed polymerizations, [3] ruthenium(0)-catalyzed coupling reactions, [4] and rhodium(I)- [5a,b] and iridium(I)-catalyzed [6] cycloaddition reactions. Examples of chiral dbCOTsa sl igandst o transition metals are, on the other hand,s carce.…”
mentioning
confidence: 99%